Generational Aspects of Inclusive Growth - Baduel, Benedicte (IMF Working Papers; Working Paper ;, 2021)
Sharing economic benefits equitably across all segments of society includes addressing the specific challenges of different generations. At present, youth and elderly are particularly vulnerable to poverty relative to adults in their middle years. Broad-based policies should aim to foster youth integration into the labor market and ensure adequate income and health care support for the elderly. Turning to the intergenerational dimension, everyone should have the same chances in life, regardless of their family background. Policies that promote social mobility include improving access to high-quality care and education starting from a very early age, supporting lifelong learning, effective social protection schemes, and investing in infrastructure and other services to reduce spatial segregation.